PASEMAYAN PAWIWAHAN DALAM PERKAWINAN HUKUM ADAT BALI - Prasada, Dewa Krisna (VYAVAHARA DUTA, 2021)
Marriage in Balinese customary law is known as pawiwahan or wiwaha.  Marriage in national law is regulated in Law Number 1 of 1974. The biggest problem in marriage is divorce which ends in conflict over property, both congenital and collective assets.  Preventive action to prevent the above problems is by making a marriage agreement.  This research focuses on normative legal research type that puts emphasis on the vagueness of norms in the marriage law regarding marriage agreements and explores more clearly the form and content of the marriage agreement in Balinese customary law.  The result of this research is a form of marriage agreement, which is a written agreement made and legalized by a notary before the marriage is conducted.  The contents of the marriage agreement include the classification of inherited and joint assets of the parties.  In the making of this marriage agreement, good consequences are considered legally, psychologically, sociologically and culturally by the existence of this marriage agreement legal action. Keywords: Agreement, Marriage, Property